RETRACTED: Financial Risk, Renewable Energy Technology Budgets, and Environmental Sustainability: Is Going Green Possible? - Ahmad, Mahmood; Ahmed, Zahoor; Gavurova, Beata; Oláh, Judit (Frontiers in Environmental Science, 2022)
Since the industrial revolution, countries have been facing the issue of climate change and environmental degradation. It is widely believed that the investment in research and development of renewable energy can play a pivotal role in fighting against climate change. However, the financial risk also increases, which can influence renewable energy technology R&D budgets and environmental sustainability. Nevertheless, the current literature is silent on the linkage between financial risk, renewable energy technology budgets, and environmental quality. Against this backdrop, this article attempts to explore the dynamic linage between financial risk, renewable energy technology budgets, and ecological footprint under the Environment Kuznets Curve (EKC) framework in Organization for Economic Cooperation and Development (OECD) countries. For this purpose, yearly data from 1984 to 2018 is employed using the advanced panel data estimation methods that address the slope heterogeneity and cross-sectional dependence issues. The results indicate that improvement in the financial risk index significantly decreases footprints, and renewable energy technology budgets also promote environmental sustainability. Economic globalization poses a significant negative effect on the ecological footprint, while energy consumption adds to the footprint. Moreover, the findings validated the EKC hypothesis in OECD countries. In addition, a unidirectional causality is detected from financial risk to renewable technology energy budgets, while bidirectional causality exists between financial risk and ecological footprint, and between financial risk, and economic growth. Based on the empirical findings, policy suggestions are presented to promote environmental sustainability.